2020
DOI: 10.1038/s41590-020-0634-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-catalytic ubiquitin binding by A20 prevents psoriatic arthritis–like disease and inflammation

Abstract: A20 is an anti-inflammatory protein that is strongly linked to human disease. Here we find that mice expressing three distinct targeted mutations of A20’s ZF7 ubiquitin binding motif uniformly developed digit arthritis that shares features with psoriatic arthritis, while mice expressing point mutations in A20’s OTU or ZF4 motifs did not exhibit this phenotype. Arthritis in A20 ZF7 mice required T cells and MyD88, was exquisitely sensitive to tumor necrosis factor (TNF) and interleukin 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…Previous studies established A20 as an inhibitor of TNF-induced cell death [58][59][60][61][62]68 . Via its ubiquitin binding domain ZnF7, A20 is believed to stabilize M1-linked ubiquitin chains in TNFR1induced complex I, which may restrict complex II formation and thereby apoptosis and/or necroptosis as shown in MEFs 58 , macrophages 59 , and intestinal epithelial cells 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies established A20 as an inhibitor of TNF-induced cell death [58][59][60][61][62]68 . Via its ubiquitin binding domain ZnF7, A20 is believed to stabilize M1-linked ubiquitin chains in TNFR1induced complex I, which may restrict complex II formation and thereby apoptosis and/or necroptosis as shown in MEFs 58 , macrophages 59 , and intestinal epithelial cells 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Several A20-dependent mechanisms to limit TNF-induced cell death have previously been reported [58][59][60][61][62] . In complex I, A20 binds and stabilizes M1-ubiquitin chains, which may limit formation of death-inducing complex II 58,59,61,62 . In addition, A20 integrates into the downstream necrosome and restricts RIPK3 activation to limit necroptosis 60 .…”
Section: Rapid Induction Of A20 Transiently Inhibits the Ripk1-ripk3 mentioning
confidence: 99%
“…3 b-c). More recently, it has been shown that A20 restricts Th17 cell expansion and arthritis through its ZnF7 motif [ 28 ].
Fig.
…”
Section: Mechanism Of A20 Regulating Arthritismentioning
confidence: 99%
“…In vitro studies suggest that A20 restricts NF-κB signals via C103-based DUB activity, while in vivo, DUB activity does not play a role in directly inhibiting NF-κB and is dispensable for the regulation of NF-κB signaling [ 15 ]. Interestingly, a recent study showed that A20’s ZnF7 domain probably also directly regulates NF-κB signaling and that it is independent of A20’s C103-based deubiquitinating activity [ 28 ]. A mixture of K63-linked and M1-linked Ub chains exists in IKK complexes, which could be recognized by ZnF4 and ZnF7, resulting in the restriction of IKKγ activity.…”
Section: Mechanism Of A20 Regulating Arthritismentioning
confidence: 99%
See 1 more Smart Citation